Optimal Design of Variable-Stiffness Fiber-Reinforced Composites - Evangelos P. Hadjigeorgiou; Christos A. Patsouras; Vassilios K. Kalpakides (Mathematics, 2025)
The concept of variable-stiffness composites allows the stiffness properties to vary spatially in the material. In the case of fiber-reinforced composites, the mechanical properties of the composite can be improved by tailoring the fiber orientations in a spatially optimal manner. In this paper, the problem of optimal spatial orientation of fibers in a two-dimensional composite structure under in-plane loading is studied, using the strain energy-minimizing method. The fiber orientation is assumed to be constant within each element of the model but varies from element to element. The optimal design problem is solved numerically using a global optimization method based on a genetic algorithm. Some numerical examples illustrate the efficiency and applicability of the method.